The Ever-Growing Puzzle of Asynchronous Release - Rozov, Andrei; Bolshakov, Alexey P.; Valiullina-Rakhmatullina, Fliza (Frontiers in Cellular Neuroscience, 2019)
Invasion of an action potential (AP) to the presynaptic terminals triggers calcium dependent vesicle fusion in the relatively short time window, about a millisecond, after the onset of AP. This allows fast and precise information transfer from neuron to neuron by means of synaptic transmission and phasic mediator release. However, at some synapses a single action potential or a short burst of action potentials can generate delayed or asynchronous synaptic release lasting for tens or hundreds of milliseconds. Understanding the mechanisms underlying asynchronous release is important, since asynchronous release can better recruit extrasynaptic metabotropic receptors and maintain a high level of neurotransmitter in the extracellular space for a substantially longer period of time after presynaptic activity. Over the last decade substantial work has been done to identify the presynaptic calcium sensor that may be involved in asynchronous release. Several models have been suggested which may explain the long lasting presynaptic calcium elevation. However, the presynaptic mechanisms underlying asynchronous vesicle release are still not well understood. In this mini-review, we overview the current state of knowledge on the molecular components involved in delayed vesicle fusion and in the maintenance of sufficient calcium concentration to trigger asynchronous release. In addition, we discuss possible alternative models that may explain intraterminal calcium dynamics underlying asynchronous release.